A perspective on the production of hydrogen from solar-driven thermal decomposition of methane. (6th October 2021) - Boretti, Alberto
Abstract: In addition to "green" hydrogen from electrolysis of the water molecule with solar-photovoltaic or wind electricity, and "white" hydrogen, based on solar-thermal driven thermochemical splitting of the water molecule, there is another emerging opportunity to produce CO2 free hydrogen at a reduced cost. The perspective advocates in favor of "aquamarine" hydrogen, based on the solar-thermal driven thermal decomposition of methane. This pathway has an energy requirement that is much less than white and green hydrogen, and even if based on hydrocarbon fuel, has no direct production of CO2 as a by-product, but rather carbon particles of commercial interest. Catalytic methane decomposition can be based on self-standing/supported metal-based catalysts such as Fe, Ni, Co, and Cu, metal oxide supports such as SiO2, Al2 O3, and TiO2, and carbon-based catalysts such as carbon blacks, carbon nanotubes, and activated carbons, the pathway of higher technology readiness level (TRL). Thus, catalytic methane decomposition appears to be a highly promising approach, with undoubtedly many challenges, but also huge opportunities following pathways to be further refined through research and development (R&D). Graphical abstract: Image 1